Memotivasi Belajar Sejarah Kebudayaan Islam dengan Metode Role Playing: Motivating Learning the History of Islamic Culture using the Role Playing Method - Mutiara, Isnaeni; Dian Rif'iyati (DIRASAH: Jurnal Kajian Islam, 2025)
The purpose of this research is to increase the motivation to learn Islamic cultural history using the role playing method in Madrasah Ibtidaiyah, creating learning that is more effective and not boring. This type of research is descriptive qualitative, which is collected from several research books and journals. The research data analysis technique uses deductive qualitative analysis techniques. According to the results of the study show that students are more motivated to learn Islamic cultural history with the role playing method than using the usual method, students are more able to express themselves in role playing, more immersed and as if plunged into the history.